Investigating Genetic Causes of Mendelian Congenital Myopathies - Dofash, Lein (Curtin University, 2022)
This thesis investigates the genetic aetiology of congenital myopathy in families with an unresolved genetic diagnosis. In two families, massively parallel sequencing and functional analyses identified two genetic candidates: a regulatory variant (c.*152G>T) and multi-exon deletion in a known disease gene (KLHL40), and a homozygous missense variant (c.1339T>C) in HMGCS1, a novel disease gene. This work supports the further investigation of regulatory variants for congenital myopathy screening and highlights the mevalonate pathway in muscle function.